Enhancement of the Josephson current by magnetic field in superconducting tunnel structures with a paramagnetic spacer - Krivoruchko, V.N.; Koshina, E.A. (Физика низких температур, 2005)
The dc Josephson critical current of a (S/M)IS tunnel structure in a parallel magnetic field is
investigated (here S is a superconductor, S/M is a proximity-coupled S and paramagnetic metal M
bilayer, and I is an insulating barrier). We consider the case when, due to Hund’s rule, in the
metal M the effective molecular interaction aligns the spins of the conduction electrons
antiparallel to the localized spins of magnetic ions. It is predicted that for the tunnel structures
under consideration there are conditions such that the destructive action of the internal and the
applied magnetic fields on Cooper pairs is weakened, and increase of the applied magnetic field
causes field-induced enhancement of the critical tunnel current. The experimental realization of
this interesting effect of the interplay between superconductivity and magnetism is also discussed.